Predictors and lesion patterns of dysphagia and swallowing outcomes after acute intracerebral hemorrhage - Xiao Hu; Min Wang; Zijie Wang; Yanfang Xie; Mengqiu Zhang; Shanyu Zhang; Tiannan Yang; Chuanqin Fang; Libo Zhao; Yanghua Tian; Qi Li (Therapeutic Advances in Neurological Disorders)
Background: Dysphagia is a common complication following intracerebral hemorrhage (ICH) and is associated with an increased risk of aspiration pneumonia and poor outcomes. Objectives: This study aimed to explore associated lesion patterns and contributing factors of post-ICH dysphagia, and predict dysphagia outcomes following ICH. Design: A multicenter, prospective study. Methods: Patients with ICH from two stroke centers within 72 h of symptom onset received baseline bedside swallowing evaluations. Dysphagia-related lesion patterns were identified using support-vector regression-based lesion-symptom mapping. Predictors of swallowing impairment on the 7th and 30th day, as well as stroke-associated pneumonia (SAP), were determined through multiple logistic regression analyses, and nomograms were developed. Results: A total of 153 patients were included in the final analysis. Of those, 28 had dysphagia. Dysphagia-related lesions predominantly affected bilateral subcortical and adjacent cortical regions. Stroke severity, hematoma expansion, and basal ganglia hemorrhage were significantly associated with initial dysphagia. Baseline aspiration risk and age were identified as independent predictors of impaired swallowing function on days 7 and 30, and SAP. Moreover, ICH volume was significantly correlated with swallowing impairment on day 7 and SAP occurrence. Midline shift and basal ganglia hematoma remained independent predictors of impaired swallowing on day 30. Predictive models for swallowing impairment on days 7 and 30, as well as SAP, demonstrated strong calibration and discriminatory ability, with C indices of 0.867, 0.895, and 0.773, respectively. Conclusion: Post-ICH dysphagia can be predicted based on stroke severity, hematoma expansion, and basal ganglia hemorrhage. Incorporating aspiration risk and imaging evaluation can further improve the identification of patients at high risk for swallowing impairment at both 1 week and 1 month after ICH.